Body and functional capacity of Lithuanian deaf basketball team players and characteristics of game indices - Milašius, K.; Paulauskas, R.; Dadeliene, R.; Satas, A. (Baltic Journal of Sport and Health Sciences, 2014)
Background. The purpose of the present study was to establish and evaluate body capacity and functional capacity of Lithuanian deaf basketball national team players, 2013 Deaflympic champions, and to provide the data analysis of the players` participation in Deaflympic Games comparing it with the data of participation in the Games of 2005 and 2009. Deaflympic Games comparing it with the data of participation in the Games of 2005 and 2009. Methods. The group of investigated persons included 12 Lithuanian deaf basketball national team members. Basketball players` body development, body and functional capacity testing was performed. Method of systemic analysis was employed to perform comparative analysis of Lithuanian deaf basketball national team players` game indicators. Results. The results of our research showed that body development and physical capacity indices of Lithuanian deaf basketball national team players who participated in 2013 Deaflympic Games allowed accomplishing the technical and tactical requirements of contemporary basketball for players of such level. Lithuanian deaf basketball national team members have demonstrated better results in muscle mass and reached higher physical capacities comparing to those of the participants of the previous Games. This increase resulted in improved quality of the game and for the first time becoming gold medals winners. Conclusion. Comparative analysis of game indices of the teams having participated in various Games showed that the majority of the competitive activity indices were better in 2013 Games in Sofia: field of goals precision was 49.2%, the high number of defensive rebounds and less turnovers during competitions allowed very effective fast breaks.